Inhibition of the Quorum Sensing System (ComDE Pathway) by Aromatic 1,3-di-m-tolylurea (DMTU): Cariostatic Effect with Fluoride in Wistar Rats - Kaur, Gurmeet; Balamurugan, P.; Princy, S. Adline (Frontiers in Cellular and Infection Microbiology, 2017)
Dental caries occur as a result of dysbiosis among commensal and pathogenic bacteria leading to demineralization of enamel within a dental biofilm (plaque) as a consequence of lower pH in the oral cavity. In our previous study we have reported 1,3-disubstituted ureas particularly, 1,3-di-m-tolylurea (DMTU) could inhibit the biofilm formation along with lower concentrations of fluoride (31.25 ppm) without affecting bacterial growth. In the present study, RT-qPCR analysis showed the target specific molecular mechanism of DMTU. In vivo treatment with DMTU, alone or in combination with fluoride, resulted in inhibition of caries (biofilm development of S. mutans) using a Wistar rat model for dental caries. Histopathological analysis reported the development of lesions on dentine in infected subjects whereas the dentines of treated rodents were found to be intact and healthy. Reduction in inflammatory markers in rodents’ blood and liver samples was observed when treated with DMTU. Collectively, data speculate that DMTU is an effective anti-biofilm and anti-inflammatory agent, which may improve the cariostatic properties of fluoride.